Effects of diluent on laminar burning speed and flame structure of gas to liquid fuel air mixtures at high temperatures and moderate pressures. (1st November 2018) - Wang, Ziyu; Bai, Ziwei; Yelishala, Sai C.; Yu, Guangying; Metghalchi, Hameed
Highlights: Effect of diluent (EGR) on flame morphology of GTL/air mixture is investigated. Hydrodynamic and thermo-diffusive effects are evaluated on flame stability analysis. Laminar burning speeds are calculated using a thermodynamic multi-shell model. Effect of diluent (EGR) on burning speed of GTL/air is investigated. Power law correlations are developed for GTL/air/diluent flame. Abstract: Gas to liquid (GTL) fuel has gained attention recently because of its clean combustion behavior. Experimental studies have been performed to investigate fundamental combustion characteristics such as laminar burning speed and flame structure of GTL/air/diluent premixed flames. In the present study, the GTL fuel was designated by Syntroleum S-8, supplied by US Air Force Research Laboratory (AFRL), which was synthesized from natural gas using the Fisher–Tropsch (F–T) process. A mixture of 32% iso -octane, 25% n-decane and 43% n-dodecane by volume was used as a surrogate for GTL fuel. In this work, two diluent concentrations of 5% and 10% were used. The diluent is a blend of 86% N2 and 14% CO2 having the same specific heat as the burned gases. Experiments were conducted using a spherical vessel for laminar burning speeds measurement and a cylindrical vessel to investigate the flame structures. The cylindrical vessel was set up in a Z-shape Schlieren system coupled with a high-speed CMOS camera that was used to capture evolutionary behavior of flames at up to 40, 000 frames per second. A multi-shell thermodynamic model was used to calculate the laminar burning speed for the smooth and low stretch flames. During the flame expansion, measured pressure rise as a function of time was the input into the thermodynamic model. Power law correlations for laminar burning speeds of GTL/air/diluent premixed flames over a wide range of temperatures (from 490 K to 610 K), pressures (from 0.5 atm to 3.2 atm), equivalence ratios (from 0.7 to 1.2), and two different diluent concentrations of 5% and 10% have been reported. Experimental burning speed results were compared with simulation values calculated by the solution of one dimensional steady premixed flame code from CANTERA using Ranzi's chemical kinetics mechanisms. Results of simulations are close to the measured values.